Two studies of women's retirement incomes in Australia: assessing some outcomes of pluralism in economic research - Jefferson, Therese (Oxford University Press, 2006)
To illustrate the potential use of plural research methods, two studies of Australian women's retirement incomes are examined. The first study employed quantitative microsimulation techniques. Its outcomes emphasised low lifetime earnings as a cause of women's lower retirement incomes. The second study used an inductive approach known as grounded theory, and its conclusions emphasised household decision-making processes as a cause of both women's low lifetime earnings and lower retirement incomes. Using Runde's criteria for assessing causal explanations, a comparison is made of the outcomes of the two studies. The conclusion is that, rather than being seen as competing accounts, the outcomes of the two varying research methods can be viewed as complementary. By demonstrating the different insights afforded by contrasting research methods, this paper provides some support for pluralism of research methods within the discipline of economics.